1975
DOI: 10.1093/ajcn/28.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Depressed cell-mediated immunity in megaloblastic anemia due to folic acid deficiency

Abstract: Cell-mediated immunity has been studied in patients with 1) megaloblastic anemia of folic acid deficiency, 2)megaloblastic anemia of pregnancy, or 3) iron-deficiency anemia. Using dinitrochlorobenzene skin tests, phytohemagglutinin-stimulated lymphocyte transformation, and rosette inhibition by antilymphocyte globulin, we have shown that cell-mediated immunity is depressed in megaloblastic anemia due to folate deficiency; this depression was reversed by folate treatment. Cell-mediated immunity was not impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…Among the B vitamins, riboflavin deficiency impairs the generation of a humoral antibody response, vitamin B-6 deficiency reduces lymphocyte maturation and diminishes antibody production, and vitamin B-12 deficiency impairs neutrophil function (30). Among certain minerals, folic acid deficiency depresses the cell-mediated immunity response (31), zinc deficiency decreases lymphocyte concentrations (32), copper deficiency reduces the cytokine response (33), and selenium is needed for proper functioning of neutrophils and T lymphocytes (34).…”
Section: Micronutrients In the Pre-haart Eramentioning
confidence: 99%
“…Among the B vitamins, riboflavin deficiency impairs the generation of a humoral antibody response, vitamin B-6 deficiency reduces lymphocyte maturation and diminishes antibody production, and vitamin B-12 deficiency impairs neutrophil function (30). Among certain minerals, folic acid deficiency depresses the cell-mediated immunity response (31), zinc deficiency decreases lymphocyte concentrations (32), copper deficiency reduces the cytokine response (33), and selenium is needed for proper functioning of neutrophils and T lymphocytes (34).…”
Section: Micronutrients In the Pre-haart Eramentioning
confidence: 99%
“…La deficiencia de hierro no altero, en esta serie, la capacidad de los lactantes a sensibilizarse con DNCB, hecho que indicaria que no existiria una altcraci6n en el reconocimiento y procesamiento antige"nico. Este hallazgo es concordante con observaciones en que 100% de un grupo de adultos deficientes en hierro fueron capaces de responder al DNCB, mientras en la deficiencia de acido f61ico solo el 4% tuvo una reacci6n cutanea positiva 26 . La respuesta cutanea significativamente menor de estos lactantes con anemia al PPD persistio despues del tratamiento co hierro, lo que hace poco probable que sea causada por la carencia de este nutriente.…”
Section: An6micosunclassified
“…Two recent reports have suggested that folate deficiency may be associated with impaired cell-mediated immunity and with impairment of mental development in children of affected mothers (Gross et al, 1974(Gross et al, , 1975. In both groups, taken from a population in which folate deficiency is common and B12 deficiency rare, the diagnosis was supported by low serum folates in the presence of a megaloblastic bone marrow, but erythrocyte folate and dU suppression were not measured.…”
Section: Miscellaneousmentioning
confidence: 99%